Implementation of a problem-based learning model assisted with scaffolding to improve scientific literacy and student cognitive learning outcomes - Intan Nurnilam Sari; Susriyati Mahanal; Deny Setiawan (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2024)
Scientific literacy needs to be developed to face the 21st century, but in Indonesia, students' scientific literacy is in the low category. The results of the preliminary study test for class Based on the facts and problems found, the research aims to improve students' scientific literacy and cognitive learning outcomes through the application of the PBL model assisted by scaffolding. This research is Classroom Action Research (CAR) with the stages of the plan, act observe, and reflection. This research was carried out for two cycles with material on the respiratory and excretory systems. The research was conducted from February to May 2023 in class XI MIPA 1 Malang Islamic High School with research subjects of 34 students. The instruments were five scientific literacy essay questions and ten multiple-choice test questions on cognitive process dimensions. The N-gain value calculates increased scientific literacy and cognitive learning outcomes. This research shows that students' scientific literacy increased from 70.4 to 81.3, so the N-gain value for scientific literacy was 0.37. Students' cognitive learning outcomes rose from 78.8 to 86.4, so the N-gain cognitive learning outcomes were 0.36. Mastery of high scientific and cognitive literacy makes students careful in making decisions with scientific considerations.Abstrak. Literasi sains perlu dikembangkan guna menghadapi abad ke-21, namun di Indonesia literasi sains siswa dalam kategori rendah. Hasil tes studi pendahuluan kelas XI MIPA 1 SMA Islam Malang rata-rata nilai literasi sains sebesar 48.5 dan rata-rata nilai ketuntasan hasil belajar kognitif hanya 15.0. Berdasarkan fakta dan masalah yang ditemukan maka tujuan dari penelitian adalah meningkatkan literasi sains dan hasil belajar kognitif siswa melalui penerapan model PBL berbantuan scaffolding. Penelitian ini merupakan Penelitian Tindakan Kelas (PTK) dengan tahapan plan, act and observe, dan reflection. Penelitian ini dilakukan sebanyak II siklus dengan materi sistem respirasi dan ekskresi. Penelitian dilakukan pada bulan Februari-Mei 2023 pada kelas XI MIPA 1 SMA Islam Malang dengan subyek penelitian 34 siswa. Instrumen yang dipakai adalah 5 soal essay literasi sains dan 10 soal tes pilihan ganda dimensi proses kognitif. Peningkatan literasi sains dan hasil belajar kognitif dihitung dengan nilai N-gain. Hasil penelitian ini memperlihatkan bahwa literasi sains siswa meningkat dari 70.4 menjadi 81.3, sehingga nilai N-gain literasi sains sebesar 0.37. Hasil belajar kognitif siswa meningkat dari 78.8 menjadi 86.4, sehingga hasil N-gain hasil belajar kognitif sebesar 0.36. Penguasaan literasi sains dan kognitif tinggi membuat siswa cermat dalam pengambilan keputusan dengan pertimbangan sains.